Long term WEB results - still going strong at 5 years? - Alpay, Kemal (SAGE PUBLICATIONS INC, 2025)
Objective: The aim of our multi-center study is to examine 5-year radiological outcomes of intracranial aneurysms (IAs) treated with the Woven EndoBridge (WEB).
Methods: All patients treated with WEB between January 2013 and December 2016 were included. Patient and aneurysm characteristic data was collected from the electronic patient record. Aneurysm occlusion was assessed using a 3-grade scale: complete occlusion, neck remnant, and aneurysm remnant. Complete occlusion and neck remnant were considered as adequate occlusion, whereas aneurysm remnant was assessed as an inadequate occlusion.
Results: A total of 66 patients (72.7% female) with 66 IAs (n = 25 acutely ruptured) were treated with WEB. The mean age of patients was 55.6 years (range: 36-71 years). The mean width of the aneurysm neck was 4.5 mm (range: 2-9 mm). 5-year imaging follow-up data was not available for 16.6% patients (n = 11). During the follow up period, 14.5% of IAs (n = 8/55) required retreatment within 24 months of initial treatment with the WEB. A total of 55 IAs were analyzed for 5-year radiological outcome. Of these, including IAs required retreatment, 47.3% of IAs (n = 26/55) were occluded completely, 36.4% (n = 20/55) had neck remnant and 16.3% (n = 9/55) had recanalized. 83.7% of IAs were occluded adequately. None of the IAs rebled after initial treatment with WEB.
Conclusion: WEB can provide acceptable adequate occlusion rates at 5 years. Furthermore, recanalization appears to be unlikely after the first two years post-treatment. The results of large studies are needed to confirm these promising long term radiological outcomes.